Sorption and desorption kinetics of nitroglycerin and 2, 4-dinitrotoluene in nitrocellulose and implications for residue-bound energetic materials. (1st January 2018) - Kuo, Dave T.F.; Simini, Michael; Allen, Herbert E.
Abstract: Energetic materials (EMs) bound to propellant residues can contribute to environmental risk and public health concerns. This work investigated how nitrocellulose, a common binding material in propellants, may control the release dynamics of nitroglycerin (NG) and 2, 4-dinitrotoluene (2, 4-DNT) from propellant residues. Batch adsorption/desorption experiments on nitrocellulose and re-interpretation on results from past leaching studies involving propellant-bound EMs were conducted. Mechanistic modeling of adsorption/desorption kinetics based on intra-particle diffusion (IPD) predicted aqueous intrinsic diffusivities ( D iw ) to within a factor of 2 of expected values. Furthermore, the IPD model was able to predict effective diffusivities ( D eff ) during the early leaching of NG from propellant residues to within a factor of 2 over a 3-log unit range. Prediction of leaching D eff 's associated with fired residues was less successful probably due to the neglect of compositional and morphological heterogeneity within the residues. Close correlations were found between the early and late D eff 's of residue-bound NG and between the fast- and slow-domain rate constants for both EMs, suggesting that the late leaching kinetics of bound-EMs may be empirically assessed from the early kinetics. This work illustrates that, in addition to dissolution, retarded diffusion through nitrocellulose matrix may also limit the overall release and transformation of residue-bound EMs in the field. Implications and limitations of the current study, and the steps forward are also presented. Graphical abstract: Image 1 Highlights: Sorption/desorption kinetics of EMs can be modeled with intra-particle diffusion. Leaching kinetics of bound-EMs may be assessable from the early kinetics. Retarded diffusion through nitrocellulose can influence release of residue-bound EMs.